2010
DOI: 10.1038/cdd.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NF-κB/miR-448 regulatory feedback loop in chemotherapy-induced epithelial–mesenchymal transition of breast cancer cells

Abstract: The epithelial-mesenchymal transition (EMT) induced by chemotherapeutic agents promotes malignant tumor progression; however, the mechanism underlying the drug-induced EMT remains unclear. In this study, we reported that miR-448 is the most downregulated microRNA following chemotherapy. Suppression of miR-448 correlated with EMT induction in breast cancer in vitro and in vivo. With the use of chromatin immunoprecipitation-seq analysis, we demonstrated that miR-448 suppression induces EMT by directly targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 40 publications
8
130
0
Order By: Relevance
“…As FOXP3 loss appears to occur more frequently in primary breast cancer cells than does SATB1 induction (Zuo et al, 2007b;Han et al, 2008), other mechanisms that participate in the suppression of SATB1 such as miR-488 may also need to be lost for SATB1 induction to occur (Li et al, 2010a). Together, these findings indicate that SATB1 expression is tightly regulated in breast epithelia both through transcriptional control and post-transcriptionally through miRs.…”
Section: Discussionmentioning
confidence: 58%
“…As FOXP3 loss appears to occur more frequently in primary breast cancer cells than does SATB1 induction (Zuo et al, 2007b;Han et al, 2008), other mechanisms that participate in the suppression of SATB1 such as miR-488 may also need to be lost for SATB1 induction to occur (Li et al, 2010a). Together, these findings indicate that SATB1 expression is tightly regulated in breast epithelia both through transcriptional control and post-transcriptionally through miRs.…”
Section: Discussionmentioning
confidence: 58%
“…It is upregulated in breast cancer (24) and early cerebral aneurysm (12), and downregulated in hepatocellular carcinoma (25) . It has also been reported that miR-448 is the most downregulated microRNA following chemotherapy in breast cancer (13), suggesting that it may act as an oncogene or anti-oncogene in different cancers. The results of the present study suggest that the expression of miR-448 in OSCC tissues was significantly higher than that in matched paraneoplastic normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…miR-448 is reportedly associated with various human malignancies. It is upregulated in breast cancer and early cerebral aneurysm (12,13), indicating regulatory effects of miR-448 in various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activation of NF-kB was frequently observed in cancers and was reported to be involved in metastasis (Karin, 2006;Van Waes, 2007;Sethi et al, 2008). It has been revealed that NF-kB can form a positive feedback loop with miR-448 through EMT to regulate metastasis in chemotherapy response (Li et al, 2011). Adriamycin-activated NF-kB directly binds the promoter of miR-448 to suppress its transcription.…”
Section: Mir-29a Regulates Emt/met By Targeting Tristetraprolin (Ttp)mentioning
confidence: 99%